Honor Culture and Body Politics in Mimpi Gadis Pasir: An Existentialist Feminist Reading - Rina Khuzaimah Basri Basri; Mahmudah; Hajrah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines gender injustice in the short story collection Mimpi Gadis Pasir through Simone de Beauvoir’s existentialist feminist perspective, especially the concept of the Other. Using a qualitative approach and textual analysis, this study explores how honor culture (bhâghus) shapes the representation of women in the text. The findings show that gender injustice is constructed through four interconnected dimensions: body politics, moral stigmatization, structural subordination, and violence. These dimensions work together in positioning women as the Other, whose identities are defined by social norms and male authority. Among these dimensions, control over women’s bodies, especially in relation to reproduction and morality, emerges as the main mechanism sustaining patriarchal dominance. Unlike previous studies that mainly view honor culture as a form of social control, this study argues that, in literary representation, honor culture also functions as a symbolic structure that shapes women’s existential condition. These findings indicate that Mimpi Gadis Pasir not only portrays gender injustice, but also offers a critical reflection on patriarchal cultural structures.